Multivariable control for a three-phase rectifier based on deadbeat algorithm - Rohten, Jaime; Zanchetta, Pericle; Rivera, Marco; Munoz, Javier; Espinoza, Jose; Silva, Jose (2016)
This paper presents a deadbeat control technique applied in a voltage source rectifier to regulate both the dc voltage (active power) and reactive power injected to the grid. As the deadbeat control is based on the system model, it leads to a faster response, without overshoot and no need to tune the controller parameters. Hence, it is used to fully control the voltage source rectifier, achieving a fast dynamic response for both the dc voltage and the power factor at the point of connection. However, there are some issues related to the high amount of power required to reach the references –especially in the dc voltage¬ in a few control steps. The proposed technique also protects the equipment by limiting the maximum power drained to/from the source. The mathematical development is made as a function of the converter power in order to limit it, but at the same time tracking the references with high dynamics, characteristic typical of deadbeat control.